Patient initiated follow up after gynaecological malignancy: National survey of current UK practice. (May 2020) - Coleman, Laura; Newton, Claire
Abstract: Objective: To establish the prevalence of follow up regimes following treatment for gynaecological malignancies in the UK. Study design: Online questionnaire Survey of gynaecological cancer centres across the UK. All members of the British Gynaecological Cancer Society (BGCS) and the National Forum of Gynaecological Oncology Nurses (NFGON) were invited to complete the survey between 12/07/2018 and 12/04/2019. Responses were grouped into cancer centres for analysis. Results: 90 % (44/49) of cancer centres from across the UK responded. All centres offer consultant follow up, most commonly for 5 years (77 %). Routine CA125 surveillance was performed for ovarian cancer in 27 % and cervical or vault cytology for cervical cancer in 9 %. Cancer centres also utilised patient initiated follow up (PIFU) (42 %), telephone follow up (36 %) and nurse led follow up (45 %). PIFU was most commonly offered in endometrial cancer (100 %) but also in vulval (26 %), cervical (32 %) and ovarian (26 %) cancer. Timing of PIFU initiation following completion of treatment varied by cancer stage and grade in endometrial cancer. For patients with grade 1 stage 1a endometrial cancer, PIFU was initiated within 3 months in 82 % of centres that use PIFU. Conclusion: Non hospital based follow up regimes are increasingly prevalent in the UK following gynaecological malignancy. The appointment and cost savings in secondary care may be significant however there is likely to be a substantial impact on the primary care sector. There is no evidence regarding the impact of PIFU on overall survival and a randomised controlled trial is strongly recommended.